2019
DOI: 10.1371/journal.pntd.0007741
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Disease Control Agents’ perception on the fight against Aedes aegypti and the prevention of arbovirus infections in Brazil

Abstract: BackgroundArboviruses pose a serious and constant threat to public health, and have demanded surveillance efforts worldwide. The prevention of arbovirus transmission depends on effective measures to control vectors and promote health. The objective of this study was to examine the factors that enhance and impair the endemic disease control agents’ field work, based on their own perspective.Methodology and main findingsIn 2017, 65 ACE of seven municipalities participated in a series of seven focus groups in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
4
0
3
Order By: Relevance
“…It is suggested that mosquito surveillance should be carried out again in Linzhi during the peak period of mosquito activity and the opening of Motuo road to obtain more accurate mosquito distribution and epidemic risk assessment of mosquito diseases. Mosquito monitoring is of great signi cance for the assessment of mosquito-borne diseases, which is consistent with the results of most studies [34] .…”
Section: Discussionsupporting
confidence: 86%
“…It is suggested that mosquito surveillance should be carried out again in Linzhi during the peak period of mosquito activity and the opening of Motuo road to obtain more accurate mosquito distribution and epidemic risk assessment of mosquito diseases. Mosquito monitoring is of great signi cance for the assessment of mosquito-borne diseases, which is consistent with the results of most studies [34] .…”
Section: Discussionsupporting
confidence: 86%
“…In addition, as has occurred in other Latin American countries, there is a growth in urban violence that has hampered entomological surveillance actions [ 28 ]. In Campina Grande, health workers reported that they were unable to enter up to 70% of households for inspection because residents were working or did not allow them to enter for fear of being robbed [ 11 ]. The authors contend that, in urban regions, the traditional model of home surveillance performed by health workers in the context of urban violence should be investigated further and include an assessment of cost-effectiveness [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This engagement has been stimulated and supported by mass media advertising, the use of breeding reporting applications (eg Zikazero) [ 9 ] and environmental education by home-visiting performed by health workers [ 7 , 10 ]. Unfortunately, in urban centres in Brazil, these visits often do not occur because residents are not in their homes or they do not allow health workers to enter for inspection and guidance on vector control for fear of violence [ 11 ]. In this context, the implementation of interventions in schools using digital platforms for mobile devices can be a powerful tool for the promotion of engagement by the population in preventive actions for arboviruses, and this can be directed by entomological surveillance services.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar dos esforços para controlar as populações de mosquitos através de medidas de controle sanitário e de vigilância epidemiológica (DONATELI et al, 2019); características de ambientes urbanos como: ocupação desordenada de áreas urbanas, dificuldade de acesso à moradia, superpopulação, além de precariedade das condições sanitárias que favorecem e amplificam e transmissão viral (LOPES;…”
Section: Introductionunclassified